Application of Compressible Multi-component Flow in Underwater Explosion Problems. (2015) - Jun, Yu; Jian-qiang, Pan; Hai-kun, Wang; Hai-bin, Mao
Abstract: High-order accurate shock-capturing schemes had been proposed to resolve compressible flow movement that involving shockwave problem in single-fluid Riemann problems previously. However, when different fluids appear, oscillations often generate at the multi-component interfaces without deep implementations. An underwater explosion (UNDEX) event is typical multi-component problem with different flows phase evolvement. In order to simulate underwater explosion, we extend the numerical schemes which include five-order WENO reconstruction and HLLC approximate Riemann solver to capture interface between the explosive gas and water. Our method is high-order accurate, quasi-conservative and interface-capturing, which has been verified by 2D problems, and produce good agreement between analytical solution and experiment result. At last we attempted to use the method to simulate shock wave loading and underwater explosion (UNDEX) near a free surface